2016
DOI: 10.5430/sass.v3n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Working Arrangement toward Organizational Commitment and Work-Family Conflict

Abstract: The purpose of this paper is to examine the relationship between flexible working arrangements and organizational commitment and work-family conflict. A total of 130 questionnaires were distributed to the finance executives and the returned yielding a response rate of 87%. The results revealed that a flexible working arrangement was significantly and positively related to organizational commitment. It also revealed that a flexible working arrangement was significantly and positively related to work-family conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
2
28
0
3
Order By: Relevance
“…In addition, Japanese companies may have reasonably adapted to Malaysian collectivism because Japanese manufacturing organizations are known for their ability to manage tacit knowledge through constructive engagement and member solidarity at the collective level (Nonaka & Takeuchi, 1995) even though nowadays Japanese management changes and parts from such family-like style due to economic stagnation and the influence of globalization (Haghirian, 2010). On the other hand, taking into account the fact that Malaysia is more developed with longer history of industrialization than most other developing countries including China and nowadays said to become more individualistic than before as a result of rapid industrialization (Choo, Desa, & Assari, 2016;Lo & Min, 2009), it is also possibly considerable that intrinsic rewards are more associated with OC than extrinsic and social rewards in line with '(i)'. Accordingly, the researcher should like to assume that intrinsic, extrinsic and social rewards have positive effects to OC in Malaysia.…”
Section: Organizational Rewards In Malaysiamentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Japanese companies may have reasonably adapted to Malaysian collectivism because Japanese manufacturing organizations are known for their ability to manage tacit knowledge through constructive engagement and member solidarity at the collective level (Nonaka & Takeuchi, 1995) even though nowadays Japanese management changes and parts from such family-like style due to economic stagnation and the influence of globalization (Haghirian, 2010). On the other hand, taking into account the fact that Malaysia is more developed with longer history of industrialization than most other developing countries including China and nowadays said to become more individualistic than before as a result of rapid industrialization (Choo, Desa, & Assari, 2016;Lo & Min, 2009), it is also possibly considerable that intrinsic rewards are more associated with OC than extrinsic and social rewards in line with '(i)'. Accordingly, the researcher should like to assume that intrinsic, extrinsic and social rewards have positive effects to OC in Malaysia.…”
Section: Organizational Rewards In Malaysiamentioning
confidence: 98%
“…Specifically, manufacturing industry experienced high rate 24% in 2013 (Towers Watson, 2013). In Malaysia it is a common complaint that employees, especially of younger generation who have grown up in highly industrialized economy and have a lot of choices to work for, are no more loyal as they used to be in the past and tend to leave their companies for slightly better pay due to low commitment to particular workplace (Choo, Desa, & Assari, 2016;Lo & Min, 2009). As Malaysia aims to transform into a high income nation by 2020 (Mahathir, 1991), it is also crucial for organizations to pay more attention to the issue of organizational commitment (OC), which is defined as the employees' state of being committed to assist in the achievement of the organization's goals, and involves the employees' levels of identification, involvement and loyalty (Caught, Shadur, & Rodwell, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The work-family conflict leads to stress, burnout, anxiety, ill-health, and some of the other working mothers' challenges (Kremer, 2016). Flexible working arrangements lead to other positive outcomes such as work commitment (Hofä cker and König 2013), work-family conflict (Choo, Desa and Asaari, 2016), and job satisfaction (Masuda et al, 2012). However, evidence from past studies has shown inconsistent and contradictory results.…”
Section: Problem Statementmentioning
confidence: 99%
“…Flexible arrangements are used as a tool or HR strategy of attracting, retaining and motivating key talented individuals. Employers encourage to offer these flexibilities due to the needs of workforce and changing environment, there are more dual earners, single parent families or women/men with elderly care responsibilities, (Choo, Desa, & Abu Hassan Asaari, 2016). (Gerdenitsch, Kubicek, & Korunka, 2015) explained that employees are given more autonomy over their jobs (when and where to work) as fixed working is now replaced by schedule working practices, employees have more options as from where to do their task (e.g.…”
Section: Flexible Working Arrangementsmentioning
confidence: 99%
“…The concept of `Work-life balance` or `work-family conflict` introduced in 1980s. Work-family conflicts increases when work interferes in family life, mostly for individuals with responsibilities toward being a guardian or care taker, (Choo, Desa, & Abu Hassan Asaari, 2016). Traditional roles suggest that men should first focus on work and women on family, as breadwinners and homeworkers respectively, but nowadays these assigned roles disdain increasingly.…”
Section: Work-life Balancementioning
confidence: 99%